Mechanical properties of rough and dehulled rice during drying - Osvaldo Resende; Paulo César Corrêa; Gabriel Henrique Horta de Oliveira; André Luis Duarte Goneli; Carmen Jarén (International Journal of Food Studies)
This work aimed to determine the mechanical properties of rough and dehulled rice grains, for different moisture contents, by obtaining their rupture force, deformation, maximum compression force and proportional deformity modulus under a compression test. Rice grains, with moisture content varying from 0.12 to 0.30 (d.b.), were subject to an uniaxial compression in order to analyze these properties. On reducting moisture content the rupture force increased from 37.2 to 70.6 N for dehulled rice and 48.0 to 79.5 N for rough rice. The average compression force varied from 131 to 171 N for dehulled rice and 203 to 283 N for rough rice. The value range of proportional deformity modulus was from 5.5 x 109 to 7.4 x 109 Pa for dehulled rice and 9.5 x 109 to 12.3 x 109 Pa for rough rice. Rough rice presented more resistance to compression compared to dehulled rice.